Elucidating the effect of tomato leaf surface microstructure on Botrytis cinerea using synthetic systems - Rombach, Helen; Alon, Haguy; Shapiro, Orr H.; Elad, Yigal; Kleiman, Maya (Frontiers in Plant Science, 2022)
For some pathogenic fungi, sensing surface topography is part of their infection strategy. Their directional growth and transformation to a new developmental stage is influenced by contact with topographic features, which is referred to as thigmo-response, the exact functionality of which is not fully understood. Research on thigmo-responses is often performed on biomimetically patterned surfaces (BPS). Polydimethylsiloxane (PDMS) is especially suitable for fabrication of BPS. Here, we used synthetic BPS surfaces, mimicking tomato leaf surface, made from PDMS with the pathogenic fungus Botrytis cinerea to study the influence of structural features of the leaf surface on the fungus behavior. As a control, a PDMS surface without microstructure was fabricated to maintain the same chemical properties. Pre-penetration processes of B. cinerea, including the distribution of conidia on the surface, germination, and germ tube growth were observed on both leaf-patterned and flat PDMS. Microstructure affected the location of immediate attachment of conidia. Additionally, the microstructure of the plant host stimulated the development of germ tube in B. cinerea, at a higher rate than that observed on flat surface, suggesting that microstructure plays a role in fungus attachment and development.